The potential capital requirement for a minimum prices insurance scheme for wheat, maize, and rape seed - Thomas Url; Serguei Kaniovski (Austrian Institute of Economic Research (WIFO), 2020)
In 2005 the EU lowered the guaranteed minimum prices for crops in its Common Agricultural Policy and stopped market interventions. Consequently, prices started to fluctuate more intensively, and farmers' incomes are now subject to higher price volatility. A crop price insurance scheme could provide an interesting instrument to stabilise the income of European farmers. We analyse the premium level and capital requirement of a hypothetical insurance contract covering several combinations of minimum prices for a bundle of wheat, maize, and rape seed. The premium level is based on the Black option pricing model and a Bayesian autoregressive stochastic volatility model. Monte Carlo simulated forecasts provide estimates for expected variances and a profit-loss distribution for various combinations of minimum prices. The required solvency capital to keep the insurance business afloat at the 1 percent ruin probability creates capital costs exceeding the expected profit.
Keywords: 330; EU-Agrarpolitik; Preisregulierung; Agrarpreis; Weizen; Mais; Raps; Agrarversicherung; Kapitalbedarf; EU-Staaten